2001
DOI: 10.1053/ejvs.2001.1405
|View full text |Cite
|
Sign up to set email alerts
|

Prospective Evaluation of Magnetic Resonance Imaging After Endovascular Treatment of Infrarenal Aortic Aneurysms

Abstract: MRI after injection of Gadolinium is more sensitive than helical CT in the detection of type II endoleaks after stentgraft implantation. Its more widespread use may permit earlier intervention in such patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
54
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 96 publications
(57 citation statements)
references
References 16 publications
3
54
0
Order By: Relevance
“…eral modalities are used, including computed tomographic angiography (CTA), magnetic resonance angiography (MRA), or ultrasound examination. [1][2][3][4][5][6][7] CTA is the most widely employed imaging modality but has the drawback of iodinated contrast. Many patients have contrast allergies or renal insufficiency that prevents the use of contrast agents.…”
Section: Fig 1ࡗthementioning
confidence: 99%
“…eral modalities are used, including computed tomographic angiography (CTA), magnetic resonance angiography (MRA), or ultrasound examination. [1][2][3][4][5][6][7] CTA is the most widely employed imaging modality but has the drawback of iodinated contrast. Many patients have contrast allergies or renal insufficiency that prevents the use of contrast agents.…”
Section: Fig 1ࡗthementioning
confidence: 99%
“…Although most centers use CTA follow-up for AAA patients, MRI is attracting attention as a modality that may replace CTA in this application. Advantages of MRI over CTA are the lack of ionizing radiation and nephrotoxic contrast agent, increased sensitivity to endoleaks, and improved softtissue contrast which enables assessment of thrombus consistency [1]. Most publications on computerized AAA segmentation describe segmentation of the contrast-filled lumen in CTA images.…”
Section: Introductionmentioning
confidence: 99%
“…Typically, triphasic, unenhanced, arterial, and delayed phase CTA is performed for post-EVAR surveillance; however, it often fails to detect the type II endoleaks detected by MRA. 12, 18 In our study, intraoperative completion angiography identified of the pre-and post-EVAR CTA and MRA identified a contrast leakage near the 4th right LA (R4) and the 4th left LA (L4) (Figures 6B-E). The 4D-flow analysis confirmed the connection between the inflow and outflow branches, which is characteristic of a type IIb endoleak ( Figure 6F; Movie S3).…”
Section: Type IV Endoleakmentioning
confidence: 49%